ANALYSIS OF CUSTOMER SERVICE PERFORMANCE AT BANK BRI GAJAHMADA UNIT: ITS INFLUENCE ON CUSTOMER SATISFACTION - Moch. Sandy Augusta Robet; Ach. Zidani Mubarok; Fefriya Wanda Nuraini (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to analyze the performance of customer service at the BRI Bank Gajahmada Unit and its influence on customer satisfaction. The focus of this research is customer service in providing satisfaction to customers. The type of data used in this research is primary data, data obtained through interviews with customer service and several BRI bank customers in the Gajahmada unit. Customer satisfaction will be achieved when customer service provides optimal service. There are several factors that influence customer satisfaction, namely: communication skills, understanding of existing products, friendliness, speed in serving, and alertness in responding to customer complaints. The benefit of this research is that it provides an overview of the services provided to create customer satisfaction.